2014
DOI: 10.5455/aim.2014.22.259-262
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Stem Cell Publications in Iran

Abstract: Objective:The purpose of this study is to examine qualitative and quantitative states of stem cell research in Iran in order to extract information production patterns.Methods:The data were extracted by searching through the Science Citation Index (SCI) Expanded database related to January 2013. The number of published articles and frequency of their citation were used as indices of the quality and quantity of information production.Results:Total number of Iranian stem cell articles and proceedings indexed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In another study Garfield showed that articles with more authors enjoy more citation ( 19 ). However, Ahmadi et al reported that international research must be distinguished in terms of sequence of authors( 20 ). In recent years collaboration network analysis is becoming one of the scientometric indicators showing association between coauthorship networks of organizations.…”
Section: Discussionmentioning
confidence: 99%
“…In another study Garfield showed that articles with more authors enjoy more citation ( 19 ). However, Ahmadi et al reported that international research must be distinguished in terms of sequence of authors( 20 ). In recent years collaboration network analysis is becoming one of the scientometric indicators showing association between coauthorship networks of organizations.…”
Section: Discussionmentioning
confidence: 99%
“…within a given topic, field, institution, and/or country [ 1 , 8 ]. Recently, bibliometrics has been used to explore trends in biomedical, medical and environmental research fields; such as the mapping of global drinking water from 1992 to 2011 [ 8 ], air PM on the cardiovascular system [ 1 ], urban health for the period 1978–2012 [ 1 ], stem cell research in Iran [ 9 ], cardiovascular research from Latin America from 1999 to 2008 [ 10 ], and ophthalmology research from 1997 to 2009 [ 11 ]. Bibliometrics applies quantitative and statistical methods to analyze a variety of phenomena across scientific literatures.…”
Section: Introductionmentioning
confidence: 99%